Risk Factors for Epilepsy After Thrombolysis for Ischemic Stroke: A Cohort Study - Brondani, Rosane; de Almeida, Andrea Garcia; Cherubini, Pedro Abrahim; Secchi, Thaís Leite; de Oliveira, Marina Amaral; Martins, Sheila Cristina Ouriques; Bianchin, Marino Muxfeldt (Frontiers in Neurology, 2020)
Background: Acute seizure or post-stroke epilepsy after thrombolysis for acute ischemic stroke remain poorly investigated. Objective: To evaluate rates and risk factors for seizures or epilepsy development after thrombolysis for acute ischemic stroke. Methods: Retrospective cohort study of 153 patients submitted to thrombolysis. Variables studied included risk factors for stroke, and variables related to acute stroke and thrombolysis. Cox regression analysis was used to determine variables independently associated with seizures or post-stroke epilepsy. Results: Seventy-four patients (48.4%) were female; mean age was 67.2 years old (SD=13.1). Initial and three months NIHSS mean score were 10.95 (SD=6.25) and 2.09 (SD=3.55), respectively. Hemorrhagic transformation occurred in 22 (14.4%) patients. A good outcome as defined by a MRS of 0-1 was observed in 87 (56.9%) patients. Twenty-one (13.7%) patients had seizures and 15 (9.8%) patients developed epilepsy after thrombolysis. Seizures were independently associated with hemorrhagic transformation (O.R. = 3.26; 95% C.I. = 1.08-9.78; p=0.035) and with mRS ≥ 2 three months after stroke (O.R. = 3.51; 95% C.I. = 1.20-10.32; p=0.022). Very early seizures occurred more often in patients who showed favorable outcome, a finding that might reflect successful thrombolysis. Hemorrhagic transformation (O.R. = 3.55; 95% C.I. = 1.11-11.34; p=0.033) and mRS ≥ 2 at three months (O.R. = 5.82; 95% C.I. = 1.45-23.42; p=0.013) were variables independently associated with post-stroke epilepsy. In our study, independent risks factors for poor outcome in stroke thrombolysis were age (O.R. = 1.03; 95% C.I. = 1.01-1.06; p=0.011), higher NIH stroke scale (O.R. = 1.08; 95% C.I. = 1.03-1.14; p=0.001), hemorrhagic transformation (O.R. = 2.33; 95% C.I. = 1.11-4.76; p=0.024), seizures (O.R. = 3.07; 95% C.I. = 1.22-7,75; p=0.018) and large cortical area (ASPECTS ≤ 7) (O.R. = 2.04; 95% C.I. = 1.04-3.84; p=0.036). Conclusions: In our study, hemorrhagic transformation and degree of neurological compromise after thrombolysis, but not before, were independently associated with seizures or post-stroke epilepsy. Late seizures were an independent risk factor associated with worst outcome after thrombolysis therapy.